Wood-cement-steatite panels used in replacement of gypsum boards in residential and commercial buildings: contribution to the thermal mass - Viet-Anh Vu; Benoit Bissonnette; Alain Cloutier; Pierre Blanchet (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
This article reports the results of a study carried out to evaluate the influence of wood-cement-steatite partitions on the thermal performance of a small building. The interior walls of two identical 2.0 × 2.5 × 3.0 m experimental wooden frame huts (tiny houses, with one door and one window), designed and built following the National Building Code of Canada, were covered with standard gypsum boards in one case (GB hut) and a combination of gypsum boards and wood-cement-steatite panels in the other case (WCSP hut). The thermal behavior of both huts, located on the campus of Laval University, in Québec (QC), Canada was monitored over a testing period extending from mid-march to the first week of July 2019. Depending on the moment during that period (cold weather, mild weather) and the characteristics being evaluated, the temperature inside the huts was conditioned or not with an electric heater. The following parameters were recorded: outdoor temperature, the temperature inside the two huts, and, when applicable, their electricity consumption. In cold weather, the wood-cement-steatite panels contributed to reducing the electricity consumption by 5.2% over that of the reference GB hut. In mild weather, wood-cement-steatite panels were found to improve the comfort inside the test hut by leveling off the temperature variations, with reductions ranging from 0.3 °C to 3.8 °C. Both the differences in electricity consumption and indoor temperature variations were determined to be statistically significant, with p - values inferior to 0.005. The results generated in this part of the study further strengthen the potential of WCSP as a real alternative to gypsum boards for drywall partitioning in residential and commercial buildings. In addition to their many advantageous constructive properties, such as water resistance, flexural strength, screw withdrawal resistance, and fire resistance, the improvements they could yield in energy efficiency and thermal comfort make it a quite promising partitioning option.